Poverty Alleviation Model In Rural East Seram: A Case Study of Karay, Salas and Sumber Agung Villages - Ekayanti Wokanubun; Wardis Girsang (Green Publisher Indonesia, 2025)
Poverty in the district of Seram Bagian Timur (SBT) is beyond the provincial poverty rate. Several poverty factors used a deductive approach. This study used an inductive approach of about 99 respondents from rural poor households. We gathered through in-depth interviews using questionnaire tools. Data analysis uses path analysis and the software SMARTPLS4.0. Research showed that most poor rural households are deprived of clear water, sanitation, education costs and access to higher education, housing, and energy. Second, the number of children and household dependency significantly influence education and health. Third, education and health significantly influence poverty. The higher the education and health level, the lower the poverty rate. Third, poverty significantly influences food consumption patterns. Poor households consume local sago food, while not-poor households consume imported rice. Research findings imply that population control through planning family is still crucial, including education and health, to reduce poverty. Poverty reduction needs to follow food security through sago palm and prime commodity industrialization program intervention.